APOE‐modulated Aβ‐induced neuroinflammation in Alzheimer's disease: current landscape, novel data, and future perspective. (18th March 2015) - Tai, Leon M.; Ghura, Shivesh; Koster, Kevin P.; Liakaite, Vaiva; Maienschein‐Cline, Mark; Kanabar, Pinal; Collins, Nicole; Ben‐Aissa, Manel; Lei, Arden Zhengdeng; Bahroos, Neil; Green, Stefan J.; Hendrickson, Bill; et al.
Abstract Chronic glial activation and neuroinflammation induced by the amyloid‐β peptide (Aβ) contribute to Alzheimer's disease (AD) pathology. APOE4 is the greatest AD‐genetic risk factor; increasing risk up to 12‐fold compared to APOE3, with APOE4‐specific neuroinflammation an important component of this risk. This editorial review discusses the role of APOE in inflammation and AD, via a literature review, presentation of novel data on Aβ‐induced neuroinflammation, and discussion of future research directions. The complexity of chronic neuroinflammation, including multiple detrimental and beneficial effects occurring in a temporal and cell‐specific manner, has resulted in conflicting functional data for virtually every inflammatory mediator. Defining a neuroinflammatory phenotype (NIP) is one way to address this issue, focusing on profiling the changes in inflammatory mediator expression during disease progression. Although many studies have shown that APOE4 induces a detrimental NIP in peripheral inflammation and Aβ‐independent neuroinflammation, data for APOE‐modulated Aβ‐induced neuroinflammation are surprisingly limited. We present data supporting the hypothesis that impaired apoE4 function modulates Aβ‐induced effects on inflammatory receptor signaling, including amplification of detrimental (toll‐like receptor 4‐p38α) and suppression of beneficial (IL‐4R‐nuclear receptor) pathways. To ultimately develop APOE genotype‐specific therapeutics, it is critical that future studies define the dynamic NIP profile and pathways that underlie APOE‐modulated chronic neuroinflammation. <boxed-text content-type="graphic" id="jnc13072-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> In this editorial review, we present data supporting the hypothesis that impaired apoE4 function modulates Aβ‐induced effects on inflammatory receptor signaling, including amplification of detrimental (TLR4‐p38α) and suppression of beneficial (IL‐4R‐nuclear receptor) pathways, resulting in an adverse NIP that causes neuronal dysfunction. NIP, Neuroinflammatory phenotype; P.I., pro‐inflammatory; A.I., anti‐inflammatory.